PROGRAMMABLE LOGIC CONTROLLER AND SCADA SYSTEMS FOR THE CONTROL OF AUTOMATED PRODUCTION DEVICES (E Conference Zone, 2022)
The article is devoted to controllers and control systems for managing automated production devices.